The Influence of Politics on Law and Its Impact on Good Governance in Nepal - Thapa, Santa Bahadur (Prajnik Bimarsha प्राज्ञिक विमर्श, 2025)
This paper examines the relationship between politics, law, and governance in Nepal, demonstrating how political interference in law affects the country's governance system. The objectives of this paper are to understand political intervention in law in both historical and contemporary contexts in Nepal, to explore where this intervention is effective and where it is not, and the implications of this for governance outcomes. Using a qualitative research methodology, the paper presents a substantive literature review. It provides a clear delineation of the historical and contemporary contexts that shape political interference in the Nepalese justice system. The paper concludes that political interference in law consistently hinders good governance in Nepal. Political interference compounds challenges such as corruption, nepotism, and a lack of transparency and accountability. The paper emphasizes that judicial independence and impartiality are essential for maintaining the rule of law and promoting good governance.